An unusual antenatal presentation of a mature pericardial teratoma masquerading as congenital pulmonary airway malformation - Vivek Krishnan; Mohan K Abraham; Ajay Abraham; Indu Ramachandran Nair; Basil Mathews (Journal of Medical Ultrasound, 2023)
We report an antenatal presentation of a huge pericardial mature teratoma that was referred as congenital pulmonary airway malformation (CPAM) in the late third trimester of pregnancy. Initial ultrasound evaluation revealed a huge predominantly cystic lesion with mixed echogenicity in the left hemithorax. A provisional diagnosis of pleural tumor was considered in view of previous scans at 20‒28 weeks being normal and associated pleural effusion. Magnetic resonance imaging of the fetus reported the lesion to be CPAM which was supported by postnatal computed tomographic imaging done on day 2 of life. However, intraoperatively, the lesion was found to be of pericardial origin which on subsequent histopathological examination was confirmed to be mature teratoma. We recommend considering potential differential diagnosis other than CPAM, especially when the lesion is found for the first time in the late third trimester.